Eleven years consecutively coral reef rehabilitation in Tobok Batang, Bontang - Derta Prabuning; Omega Raya Simarangkir; Muhammad Naufal Prinanda; Dimas Prasetyo; Nurcahaya Nurcahaya; Fawzia Nasoetion (Depik, 2024)
Coral reefs in Tobok Batang, a nearby estuary of Bontang Regency, have a vital role in the threatened ecosystem due to non-environmental-friendly fishing practices and a global threat in the form of coral bleaching. In response to these conditions, PT Pupuk Kalimantan Timur initiated the Kilau Samudera Program to support damaged coral reef recovery through community-based rehabilitation by developing and maintaining artificial reef modules. The study objective was, therefore, to determine the rehabilitation efficacy in Tobok Batang, through (1) coral growth informed by colony diameter, and (2) targeted reef fishes informed by abundance and biomass. Data was collected by purposive sampling in eleven clusters of three modules: pyramid, dome, and cube. The result shows that coral had been found attached in all these eleven clusters, while the targeted fishes had been found in most clusters. Clusters deployed in 2015 and 2017 have an average colony diameter of 30 cm (SE), the two highest among the other clusters. The highest abundance of corallivores was found in the cluster deployed in 2017 and 2020 (9 ind/100 m2). The highest herbivore abundance also was found in the cluster deployed in 2017 and 2020 (23 ind/100 m2), while its highest biomass was found in cluster 2020 only (40 kg/100 m2). The highest carnivore abundance was found in cluster 2017 only, with four fish per 100 m2 as well as the biomass in the same cluster (9kg/100 m2). All these cluster groups have provided new habitats in shallow waters, indicating that the cluster has a good position and probably good material composition that can trigger coral juveniles to attach, settle, and grow, which also became a unique habitat for some targeted reef fish. This study showed that the location and these three modules were proven effective for rehabilitating methods in damaged coral reefs.Keywords:Coral Reef,Rehabilitation,Tobok Batang,Bontang,Reef Fish